2005
DOI: 10.1103/physrevb.72.060401
|View full text |Cite
|
Sign up to set email alerts
|

Correlations in the electronic structure of half-metallic ferromagneticCrO2films: An x-ray absorption and resonant photoemission spectroscopy study

Abstract: The electronic structure of high-quality CrO 2 ͑100͒ films was investigated by means of x-ray absorption and resonant photoemission spectroscopy at the 2p-3d excitation threshold. The obtained binding energy of the occupied Cr 3d states is in agreement with the results predicted within the local spin-density approximation using the dynamical mean-field theory ͓L. Craco et al., Phys. Rev. Lett. 90, 237203 ͑2003͔͒. The reported data support a model of CrO 2 as a half-metallic ferromagnet with strong electron-cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 21 publications
5
32
0
Order By: Relevance
“…The peak characteristics fi t well with references in the literature for Cr 2 O 3 . [39][40][41] This is confi rmed by AFM measurements, which clearly show the Cr 2 O 3 crystals on top of the TiO 2 thin fi lm (see Figure S4, Supporting Information). These results in combination with the electrical characterization suggest that Cr segregates mostly at the surface of TiO 2 and does not affect the charge transport across this layer very signifi cantly.…”
Section: Resultsmentioning
confidence: 67%
“…The peak characteristics fi t well with references in the literature for Cr 2 O 3 . [39][40][41] This is confi rmed by AFM measurements, which clearly show the Cr 2 O 3 crystals on top of the TiO 2 thin fi lm (see Figure S4, Supporting Information). These results in combination with the electrical characterization suggest that Cr segregates mostly at the surface of TiO 2 and does not affect the charge transport across this layer very signifi cantly.…”
Section: Resultsmentioning
confidence: 67%
“…So far, there are only a few XPS results that show the metallic nature of the CrO 2 thin films. 6,7 For instance, Chang et al 7 showed the valence band spectrum with a finite intensity in the region of the Fermi level in the synchrotron XPS measurements with a photon energy of 385 eV, close to the energy we used. The present results are in good agreement with their results.…”
Section: Resultsmentioning
confidence: 99%
“…Only a few exceptions have been reported. 6,7 X-ray photoelectron spectroscopy ͑XPS͒ studies of the film surface do not find a metallic Fermi edge while the film shows metallic conductivity. 8 Cheng et al 9 have reported that Cr 2 O 3 , which is an insulator and the most stable phase in chromium oxide binary system, is formed at the surface of CrO 2 thin film.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 The lineshape for both the 0/5% and 5/0% films shows clear correlation with the octahedral Cr 3+ of the Cr 2 O 3 reference spectrum, with the position of peaks A, B, and C occurring at the same energies, i.e. 578.3, 579.5, and 580.4 eV; the D peak is not as clear as all others, and occurs around at 582.2 eV.…”
Section: Chemical Environmentmentioning
confidence: 95%